Pengolahan Pepaya Muda (Carica Papaya L) Menjadi Stik Pepaya Di Kota Bengkulu - Harni, Suli; Yulista, Yulista; Pardosi, Ivan Agustinus; Delpana, Adrian; Kusuma, Arya Mufti Nata; Sumartono, Eko; Parwito, Parwito (Jurnal PADAMU NEGERI (Pengabdian pada Masyarakat Bidang Eksakta), 2023)
Papaya (carica papaya) is a fruit that is round to elongated in shape, with the tip usually tapered. The color of the fruit when young is dark green, and when ripe it is orange. Papaya fruit contains substances that are beneficial for the body and can be consumed or treated because it contains many good ingredients to protect the body from various diseases. The chemical contents of papaya are calories, water, protein, carbohydrates, fiber, potassium, calcium, magnesium, phosphorus, Vitamin A, Vitamin C, Vitamin E, niacin and folate. Papaya sap also contains papain, chemopapain, lysozyme, lipase, glutamine, and cyclotransferase. The aim of this research is to process young papaya into shredded meat that has a high taste and is healthy which can be consumed as a substitute for side dishes, and as a snack for children and adults. The samples used in this research were 1 kg of young papaya, 3 cloves of shallots, 1 clove of garlic, salt to taste which was obtained around Bengkulu City. The processing technique is done by grating, draining and fried. The research results showed thatÂ  papaya stik crispy has a high taste and produces a distinctive color, taste and aroma.Â Â